PENGEMBANGAN MODEL PERMAINAN PEMBELAJARAN BOLA BASKET DI SEKOLAH MENENGAH ATAS - Putra, Ardi Wiguna; Triansyah, Andika; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this study is that the variation in the learning model of one of the material is still very minimal so that learning related to basketball material is still not fully understood so that students are confused and feel bored in learning it. This study aims to develop a basketball learning game model in high school and find out the validity, effectiveness and response of students to the learning game model. This study was conducted in three schools, namely SMAN 1 Pontianak, SMAN 7 Pontianak and SMAN 1 Sungai Raya with the research subjects of the students of natural science class grade XI in academic yearÂ  2018/2019.The research method used is the ADDIE development model consisting of Analiysis (Analysis), Design (Design), Development (Development), Implementation (Implementation), and Evaluation (Evaluation). Upper middle class based on the assessment of the game model experts obtained a score of 34 with a percentage of 85% included in the criteria are very valid and assessment of learning experts obtained a score of 32 with a percentage of 80% included in the criteria are quite valid.The effectiveness of this learning game model obtained an effect size of 3.7 in SMAN 1 Pontianak, 1.7 in SMAN 7 Pontianak, 1.65 in SMAN 1 Sungai Raya, so the learning game model used was effective. The response of students to the basketball learning game model in high school gave a positive response with an average score percentage of 81.32%.Â Keywords: Development, Game Model, Learning, Basketball